Rekonstruksi Misi dalam Konteks Moderasi Beragama: Belajar dari Surat 1 Korintus - Saputra, Jefri Andri (Unit Penerbitan Informasi dan Teknologi Sekolah Tinggi Teologi Gereja Kalimantan Evangelis (STT GKE), 2024)
This article aims to reconstruct the church mission in the context of religious moderation. Religious moderation has led to the need to review the church's mission in the form of Christianization, stealing own, and the church's appearance in the public space that debates as conservative and liberal. This action has become a problem in the history of Christian encounters with other religions and internal church relations across denominations.The research approach in this paper is a library research. The author collected data through books and research journals related to religious moderation, missions, and the letter 1 Corinthians. The author finds that the church mission in 1 Corinthians is to be a congregation that avoids syncretism, internalizes religious identity and collective ethics, and uses love as the spirit to construct a solidary and missionary community.